2006
DOI: 10.1016/j.jom.2006.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A supplier development program: Rational process or institutional image construction?

Abstract: Drawing on arguments from institutional theory, we examine the implementation and use of a supplier development program by a major North American automotive manufacturer. While all suppliers adopted the program as an apparent response to coercive institutional pressures from their customer, the study focuses on the effects of such pressures on internal information processing and the behavior of the actors involved. The study therefore addresses a significant gap in the institutional theory literature concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 65 publications
(100 reference statements)
3
106
0
1
Order By: Relevance
“…Meyer and Rowan (1977) suggested that an organization may respond to institutional pressures through superficial conformity. This "decoupling" of pressure from expected response arises when adaptations to institutional pressures have uncertain efficiency consequences (Meyer and Rowan 1977;Rogers et al 2007; Boxenbaum and Jonsson 2008), if they contradict internal efficiency needs, i.e., create potential trade-offs in priorities (Meyer and Rowan 1977), when practices do not reflect local circumstances or realities (Scott 2008), or when there is information asymmetry between firms and their stakeholders (Crilly et al 2012). A case in point is the apparel supply chain, which included a number of incidents of social failure indicating a decoupling between the socially sustainable policies adopted by buyers and the actual implementation of socially sustainable practices in suppliers.…”
Section: Institutional Decoupling Of Socially Sustainable Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meyer and Rowan (1977) suggested that an organization may respond to institutional pressures through superficial conformity. This "decoupling" of pressure from expected response arises when adaptations to institutional pressures have uncertain efficiency consequences (Meyer and Rowan 1977;Rogers et al 2007; Boxenbaum and Jonsson 2008), if they contradict internal efficiency needs, i.e., create potential trade-offs in priorities (Meyer and Rowan 1977), when practices do not reflect local circumstances or realities (Scott 2008), or when there is information asymmetry between firms and their stakeholders (Crilly et al 2012). A case in point is the apparel supply chain, which included a number of incidents of social failure indicating a decoupling between the socially sustainable policies adopted by buyers and the actual implementation of socially sustainable practices in suppliers.…”
Section: Institutional Decoupling Of Socially Sustainable Practicesmentioning
confidence: 99%
“…However, more in-depth scrutiny is required into why firms decouple and what allows them to do so (Greenwood et al 2011). Further, Rogers et al (2007) highlighted the need to develop an improved understanding of how to cope with decoupling phenomena. More recently, Wilhelm et al (2016) asserted that there should be a special focus on the implementation and decoupling of socially sustainable practices in suppliers located in developing countries that have a different institutional context.…”
Section: Institutional Decoupling Of Socially Sustainable Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, the prevailing trend in some industries has been to reduce the number of suppliers to a few competent ones, known as rationalizing the supplier base (Batson, 2008), and improving the efficiency of those suppliers that are left; all this with the purpose of improving performance of the entire operation (Rogers, Purdy, Safayeni, & Duimering, 2007).…”
Section: Suppliers Quality Managementmentioning
confidence: 99%
“…Supplier development can go from just selecting suppliers based on conformance (narrow perspective), to efforts by the customer to improve the capabilities of suppliers (broad perspective), which usually benefit both parties (Rogers, et al, 2007). It is common, for example, among automotive companies, to have "supplier development representatives", who visit suppliers' plants regularly and teach them lean manufacturing techniques and variability-reduction methods.…”
Section: Suppliers Quality Managementmentioning
confidence: 99%